Moros y Cristianos together?: The politics of death and Muslims in Spain - Arana Barbier, Paula Maria (Ethnicities, 2025)
During the Spanish Civil War (1936-1939), General Franco recruited approximately 80,000 Moroccan Muslim soldiers to support his cause. Part of the strategy to uphold the soldiers’ morale and the image of a “joint crusade against the godless” involved incorporating Islam into the Spanish context. Services such as Muslim hospitals and cemeteries were organised, representing the largest presence of Islam in the public sphere since medieval times. Nevertheless, in the aftermath of the war and following Morocco’s independence from Spain, most of these spaces have either been forgotten, destroyed, or subjected to prolonged contestation. This article explores the evolution of these sites and the diminishing burial options for Muslims through Spain’s dictatorship and transition to democracy, explicitly illuminating how its purportedly multicultural facade has eroded. This relates to the notion of the Moor in the Spanish national imagination and how, over centuries, this imagined other has continued to serve as a scapegoat for social and political ills. As such, this article also links the contact of spatial contestations over multicultural emerging movements aimed at normalising burial practices for Muslims in Spain. Thus, allowing Spanish Muslims to live their dual identity through acts of citizenship such as being buried in their places of residence.